Platform models in small businesses: A challenge for mature companies - Rafael Dan Schur; Rodrigo Sabiá (Regepe Entrepreneurship and Small Business Journal)
Objective: Understand the necessary conditions for small companies to adopt business models based on digital platforms. Methodology: The methods of Structural Equation Modeling by Partial Least Squares (PLS-SEM) and Necessary Condition Analysis (NCA) were applied in an online survey with 126 small companies to evaluate relationships of sufficiency and necessity of selected constructs in the adoption of business models based on digital platforms. Results: The necessary condition for small businesses to adopt digital platform-based business models is that they are at an early stage of their lifecycle before and during the peak of COVID-19, which indicates that platforms represent a challenge for mature small businesses grounded in the issue of entrepreneurial inertia. Theoretical-methodological contributions: Expansion of the literature on the adoption of digital business by small companies, adding the emerging NCA methodology to the research in this field of study and supporting evidence of the existence of business inertia in mature companies. Relevance/originality: Application of the emerging NCA methodology in an original online survey for the study of digital transformation of small businesses, identifying necessary factors in the adoption of platform-based models. Social contributions: References in the literature indicate that the adoption of digital platforms is a relevant strategy to improve competitiveness and small companies need to adapt to this new business model in order to overcome the impacts of COVID-19, defeating the business inertia present in mature companies.